Pengaruh Model Pembelajaran Cooperative Learning Tipe Think Talk Write (TTW) Terhadap Pemahaman Siswa pada Mata Pelajaran Ekonomi: Penelitian - Ika Dwi Jaksana; Haeril; Muhammad Yany (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Effect of the Cooperative Learning Model of the Think Talk Write (TTW) Type on Students’ Understanding in Economics Subjects for Eleventh-Grade Students at SMK Negeri 4 Bone. Undergraduate Thesis, Economics Education Study Program, Universitas Muhammadiyah Bone. Supervised by Haeril, S.E., M.Si. (Supervisor I) and Muhammad Yany, S.E., M.Si. (Supervisor II).This study aimed to determine the effect of the Cooperative Learning model of the Think Talk Write (TTW) type on students’ understanding in economics subjects for eleventh-grade students at SMK Negeri 4 Bone. This research used a quantitative approach with an experimental research design. The population of this study consisted of 101 eleventh-grade students, while the sample was students of class XI OTKP selected through random sampling. The research variables consisted of independent and dependent variables. Data collection techniques included observation, tests, and documentation. Data analysis techniques included descriptive statistical analysis, normality testing, homogeneity testing, and hypothesis testing.The results of the study showed that the hypothesis testing produced a calculated t-value of 4.418, which was greater than the t-table value of 1.697, with a significance value of 0.000 < 0.05. This indicated that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. These findings prove that the TTW learning model has a positive effect on improving students’ understanding. Overall, this study shows that the implementation of the TTW learning model is effective in improving students’ understanding of economics subjects.